CHARACTERISTICS OF ORGANOLEPTIC QUALITY AND pHBAUNG (Mystus nemurus) WITH SOAKING IN THE CHITOSAN SOLUTION - Jhosua Fransiskus; Rahman Karnila; Andarini Diharmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThis study was aimed to determine the organoleptic quality and pH of fresh baung (Mystus nemurus) soaked with chitosan solution with different concentrations. This research used the experimental method, by immersing the fish with chitosan solution with a concentration of 0% (without chitosan), 1, 2, and 3% and soaking time 0, 4, 8 and 12, for 16 hours. The analysis parameters were consisted of organoleptics including eye appearance, gills, mucus, meat (color and appearance), odor, texture, and pH test. The results were showed that immersion of baung in high concentration of chitosan can maintain freshness of baung fish. Soaking fish in 3% chitosan solution is able to maintain freshness with freshness for 12 hours aimed at the value of the eye value of 6.79 (sunken eyes, pupils turn white, cloudy corneas); gills with a value of 7.05 (pale red color, without mucus); odor 6.87 (Neutral). Immersion in chitosan solution for 16 hours produced atexture of baung fish 7.13 (rather soft, less elastic when pressed with a finger, difficult to tear meat from the spine); meat with a value of 7.12 (less brilliant, specific type, no milking along the spine, abdominal wall of whole meat);mucus with a value of 7.05 (The mucus layer starts to become slightly cloudy, the color is rather white, less transparent); and pH 6. The best treatment for this is immersion of baung fish with a concentration of chitosan 3%. Keywords: eye,freshness, solution concentration, texture,